The Three Bears' Christmas - Duval, Kathy (Holiday House, 2005)
After taking a walk on Christmas Eve while their freshly baked gingerbread cools, Papa, Mama, and Baby Bear arrive home to encounter another "trespasser," who does not have golden hair but wears a red suit and leaves presents. Someone has eaten the three bears' gingerbread cookies. Someone has sat in their chairs and slept in their beds too! The intruder has left clothing all over the house-a woolly mitten, a black boot, and a red coat. Best of all, he's also left presents under the tree! Children will enjoy picking out the hidden clues left by Santa throughout the house and catching him making a getaway in his sleigh in just his long johns!